WAQF LAND DEVELOPMENT FOR PRIVATE TAHFIZ SCHOOLS IN THE STATE OF PERLIS, MALAYSIA: PROCEDURES AND ADVANTAGES (UUM Journal of Legal Studies, 2024)
Waqf is a state matter subject to state laws, given the position of the State Islamic Religious Council (SIRC) as the ‘sole trustee’ of waqf properties in their respective states. In legal terms, any party that intends to apply waqf and any waqf activities established in Private Tahfiz Schools (PTS) requires the permission of the SIRC. Accordingly, this study aims to examine the legal procedures for developing PTS on waqf land in Perlis, Malaysia, including the advantages of acquiring the permission of Perlis Islamic Religious and Malay Customs Council (MAIPs). The qualitative research methodology was applied in this research, which featured the doctrinal approach in examining state enactments, past studies, and semi-structured interviews involving several respondents who had extensive experiences with the subject under study. Subsequently, analysis was conducted on the collected data through the content analysis technique. The implications from this research offer numerous advantages for PTS in Perlis to ensure its sustainability. This study offers a clear understanding to individuals who intend to implement waqf in their PTS in Perlis, Malaysia.